Chia Ziri formation "U. Permian" in Iraq Reservoir characteristic, depositional facies and diaigentic control on reservoir and future oil producing - Al-Hadidy, Dr. Aboosh H. (Journal of Petroleum Research and Studies, 2017)
The Permian –Triassic Chia Ziri formation holds oil and gas reserves in exploration blocks in Iraq .Paleozoic is the most under explored succession in Iraq including important Permo-Triassic sequences. Several wells was penetrated the Chia Ziri fm. in Iraq, three wells in NW Al-Jazira area (Kd-1,Mt-1 and As-1) and south west desert blocks in the two wells (Dn-1 and Wk-1). The Chia Ziri fm. represents a Permian transgression over varied topography in Iraq. Lithologicaly, the formation is comprised of both carbonate & siliciclastic. The depositional setting was in subtidal to supratidal “shelf platform" with multiple digenetic events which control the reservoir characteristic. However, The main source rock for entire Paleozoic plays in Iraq is Lower Silurian Akkas formation and lower Chia Ziri shaley parts. Paleozoic is the most under explored succession in Iraq including important permo-Triassic sequences. The Permian –Triassic Chia Zairi formation holds oil and gas reserves in Iraq. Several wells was penetrated the Chia ziri fm, in Iraq, three wells in Nw Al-jezira area and south west desert blocks Lithologicaly,the formation is comprised of both carbonate &siliciclastic,The depositional setting was in subtidal to supratidal" shelf platform" " with multiple digentic events which control the reservoir characteristic. The main source rock for entire Paleozoic plays in Iraq are Lower Silurian Akass Fm and lower chia Zairi shale parts